Persepsi Guru terhadap Persatuan Guru Republik Indonesia dalam Meningkatkan Profesionalisme Guru - Henawanto, Anton (Program Studi Magister Pedagogi, 2014)
Anton HenawantoPGRI Kota Malange-mail: henawantoanton@yahoo.comAbstract:The research was conducted by using a qualitative approach, with descriptive to process the data. The subjects in this research were teachers, principals and administrators of the organization, to enrich the information researcher was looking for six teachers, two administrators and principals as well as two expert organizations. The Regulation of National Education Minister Number 18-2007 concerning teacher certification, it is a form of clear proof of legal certainty. The benefits of policy can be implementable perceived, through professional recognition accompanied with profession allowance of once salary every month is a logical consequence of a certified teacher who is always demanded to improve his professionalism. Recognized or not by the teacher, it has been realized by the persistence of PGRI struggle to pressure the government. Teachers' perceptions about the degree improvement and the change of teachers’ fate over the years are the goodwill of the government's efforts itself, without the involvement of PGRI.Keyword: teachers’ perception, teacher, professionalism.Abstrak:Penelitian ini dilakukan dengan menggunakan metode pendekatan kualitatif, dengan deskriftif untuk mengolah data. Subyek dalam penelitian ini adalah guru, kepala sekolah dan pengurus organisasi, untuk memperkaya informasi peneliti mencari data dari enam orang guru, dua pengurus dan kepala sekola serta dua orang pakar organisasi, total semua sepuluh orang. Permendiknas Nomor 18-2007 tentang sertifikasi guru, bentuk bukti kepastian hukum yang jelas. Kebijakan tersebut secara implementatif dapat dirasakan manfaatnya, melalui pengakuan profesional diiringi dengan tunjangan profesi sebesar satu kali gaji pokok setiap bulan, merupakan konsekwensi logis guru bersertifikat pendidik, selalu dituntut untuk meningkatkan profesionalnya. Diakui atau tidak oleh guru, hal tersebut telah teralisasi berkat kegigihan perjuangan PGRI untuk menekan pemerintah. Persepsi guru tentang peningkatan derajat dan perubahan nasib guru selama ini, merupakan goodwill dari upaya pemerintah semata, tanpa keterlibatan PGRI.Kata kunci: persepsi guru, guru, profesionalisme